A taxonomic synopsis of Chrysomydas Wilcox, Papavero & Pimentel (Diptera: Mydidae: Mydinae), with first bionomic records for the genus and description of a new species from Brazil - Calhau, Julia; Lima, Sheila; Rafael, José Albertino; Lamas, Carlos José Einicker (Zootaxa, 2019)
Chrysomydas Wilcox, Papavero & Pimentel, 1989 (Diptera, Mydidae, Mydinae, Stratiomydina), is a poorly known monotypic genus, with the type-species, C. nitidulus (Olivier, 1811), recorded from Brazil, French Guiana, Guyana, and Suriname. The present work aims to provide an updated diagnosis for the genus and type-species, C. nitidulus, along with the description of C. phoenix Calhau & Lamas sp. nov. from the state of Rio de Janeiro, Brazil, based on a male imago and associated pupal exuviae. Additionally, the first bionomic data for the genus are reported, with the rearing of adult C. nitidulus in the laboratory from larvae collected under the decaying trunk of a coconut palm (Cocos nucifera L.) in the state of Amazonas, Brazil. The new species is easily distinguished from C. nitidulus by the predominantly black tergal and scutal setulae, which are golden in the type-species. They also differ by the male genitalia and shape of the proboscis.